STUDY ON THE INFLUENCE OF WEDM PROCESSING REGIMES ON THE QUALITY OF ARMOR STEEL - OANA-GEORGETA GHIORGHE; CAROL SCHNAKOVSZKY; EUGEN HERGHELEGIU; CATALIN TAMPU (Journal of Engineering Studies and Research, 2022)
The aim of the current paper is to analyze the influence of process parameters on the dimensional accuracy of parts manufactured by Ramor 550 and Ramor 400 armored steel, using the wire electrical discharge machining (WEDM). Two working regimes were used and the processing quality were quantified by measuring the dimensional accuracy of four parameters (three lengths, an angle and a radius). The obtained results emphasized that working regime 002 leaded to larger dimensional deviations compared to working regime 001. Related to the material, the dimensional deviations were larger in case of Ramor 550 armored steel.